C-reactive protein (CRP) and serum phospholipase A2 in the assessment of the severity of acute pancreatitis. Issue 6 (June 1987) - Puolakkainen, P; Valtonen, V; Paananen, A; Schröder, T
Abstract : The present study examines the value of C-reactive protein (CRP) determinations in the assessment of the severity of acute pancreatitis and the correlation of CRP with serum phospholipase A2 activity and the clinical status. Fifty three patients with acute pancreatitis were studied; 17 with haemorrhagic pancreatitis and 36 with a mild form of the disease. S-phospholipase A2 activity increased significantly (p less than 0.05) in patients with fatal pancreatitis but not in those with mild disease. Phospholipase A2 concentrations were below 10 nmol FFA/ml min in mild, while they rose to 20-40 nmol FFA/ml min in haemorrhagic pancreatitis. In fatal cases very high (up to 50-60 nmol FFA/ml min) serum phospholipase A2 concentrations were recorded. The increase in CRP was greater in the patients with severe pancreatitis. One day after admission mean CRP was 280 mg/l in patients with haemorrhagic and 45 mg/l in those with the mild pancreatitis (p less than 0.001). High CRP values also correlated with the prognostic signs indicative of severe pancreatitis. CRP and S-phospholipase A2 determinations are valuable in the early assessment of the severity of acute pancreatitis, but the CRP assay is much easier to include in hospital routine.